-7y+12=-3(y+8)

Simple and best practice solution for -7y+12=-3(y+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7y+12=-3(y+8) equation:



-7y+12=-3(y+8)
We move all terms to the left:
-7y+12-(-3(y+8))=0
We calculate terms in parentheses: -(-3(y+8)), so:
-3(y+8)
We multiply parentheses
-3y-24
Back to the equation:
-(-3y-24)
We get rid of parentheses
-7y+3y+24+12=0
We add all the numbers together, and all the variables
-4y+36=0
We move all terms containing y to the left, all other terms to the right
-4y=-36
y=-36/-4
y=+9

See similar equations:

| -13x-26=-11x+48 | | 70y=2 | | 12/27=x/5 | | 3(5x-2)=8=x | | 2(x+8)=11x-5 | | x-8-7x=22 | | 5/x=25/21 | | 2-2n=2+17 | | 3=7p= | | 11x-11=-2x-63 | | w+235=654 | | 91=43+x | | 0=-2j+2j | | 870=5(x+19) | | 3x−9=x+3 | | 8j-9=5j+18 | | 9(x+5)=5x+33 | | 3x+3=(x+35)=705 | | 1.2x+50=3.2x | | -5x^2+27x=10−5x2+27x=10 | | 1x+1-4x+8=21 | | 58=y÷6+49 | | 1.2x=50=3.2x | | 12/27=5/x | | 4(2.5x+3.25)=25+4x | | 6(b-7)-2=10 | | 10x-3x=x+84 | | -10p-3=-6-10p | | 5x+3-24=6x-5x+7 | | 2x−4=4x−30 | | .7x-3=7x+5 | | 7y=30=-8y |

Equations solver categories